Inflation and Public Debt Reversals in Advanced Economies - Fukunaga, Ichiro (IMF Working Papers; Working Paper, 2019)
This paper quantitatively assesses the effects of inflation shocks on the public debt-to-GDP ratio in 19 advanced economies using simulation and estimation approaches. The simulations based on the debt dynamics equation and estimations of impulse responses by local projections both suggest that a 1 percentage point shock to inflation rate reduces the debt-to-GDP ratio by about 0.5 to 1 percentage points. The results also suggest that the impact is larger and more persistent when the debt maturity is longer, but the difference from the benchmark case is not significant. These results imply that modestly higher inflation, even if accompanied by some financial repression, could reduce public debt burden only marginally in many advanced economies.